Continuous Glucose Monitoring-Derived Metrics and Capillary Vessel Density in Subjects with Type 1 Diabetes without Diabetic Retinopathy. (15th April 2023) - Cutruzzolà, Antonio; Carnevali, Adriano; Gatti, Valentina; Latella, Giovanni; Lamonica, Luca; Oliverio, Flavia; Borelli, Massimo; Parise, Martina; Di Molfetta, Sergio; Scorcia, Vincenzo; Irace, Concetta; Gnasso, Agostino
Abstract : Optical coherence tomography angiography (OCTA) is an innovative and reliable technique detecting the early preclinical retinal vascular change in patients with diabetes. We have designed our study to evaluate whether an independent relationship exists between continuous glucose monitoring (CGM)-derived glucose metrics and OCTA parameters in young adult patients with type 1 diabetes without diabetic retinopathy (DR). Inclusion criteria were age ≥ 18 years, diagnosis of type 1 diabetes from ≥ 1 year, stable insulin treatment in the last three months, use of real-time CGM, and CGM wear time ≥ 70 % . Each patient underwent dilated slit lamp fundus biomicroscopy to exclude the presence of DR. A skilled operator performed OCTA scans in the morning to avoid possible diurnal variation. CGM-derived glucose metrics from the last 2 weeks were collected through the dedicated software during OCTA. Forty-nine patients with type 1 diabetes (age 29 [18; 39] years, HbA1c 7.7 ± 1.0 % ) and 34 control subjects participated in the study. Vessel density (VD) of the whole image and parafoveal retina in the superficial (SCP) and deep capillary plexus (DCP) was significantly lower in patients with type 1 diabetes compared to controls. The coefficient of variation of average daily glucose, evaluated by CGM, significantly correlated with foveal and parafoveal VD in SCP and with foveal VD in DCP. High glucose variability might be responsible for the early increase of VD in these areas. Prospective studies may help understand if this pattern precedes DR. The difference we detected between patients with and without diabetes confirms that OCTA is a reliable tool for detecting early retinal abnormalities.